1989
DOI: 10.1038/342877a0
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of immunoglobulin hypervariable regions

Abstract: On the basis of comparative studies of known antibody structures and sequences it has been argued that there is a small repertoire of main-chain conformations for at least five of the six hypervariable regions of antibodies, and that the particular conformation adopted is determined by a few key conserved residues. These hypotheses are now supported by reasonably successful predictions of the structures of most hypervariable regions of various antibodies, as revealed by comparison with their subsequently deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
707
0
5

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,145 publications
(730 citation statements)
references
References 31 publications
13
707
0
5
Order By: Relevance
“…The CDRs were determined according to Kabat, except the CDR-H1, for which the combined Kabat/Chothia definition was used (Chothia et al, 1989;Kabat and Wu, 1991). Alignment of the VH and VL amino acid sequences with the Kabat database produced maximal alignment of the murine FR with the FRs of the human B43 heavy chain and human REI light chain, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The CDRs were determined according to Kabat, except the CDR-H1, for which the combined Kabat/Chothia definition was used (Chothia et al, 1989;Kabat and Wu, 1991). Alignment of the VH and VL amino acid sequences with the Kabat database produced maximal alignment of the murine FR with the FRs of the human B43 heavy chain and human REI light chain, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, during recombination events, nucleotides can be randomly deleted from or added to the ends of the gene segments, leading to length variation and even greater diversity. As a result, CDR H3 is found with medium or large surface loops with very different sequences and patterns of interaction (30). Thus, it is not surprising to see that extra flexibility is programmed into CDR H3 of the germline antibody to expand the structural diversity of the primary repertoire beyond that generated by sequence diversity alone.…”
Section: Resultsmentioning
confidence: 99%
“…L 1 and H 1 connect strands of differ- ent sheets within the VL and VH domains, respectively. It has been suggested by Chothia et al (1989) that antibodies have only a few main chain conformations or canonical structures for some of the hypervariable loops Figure 6 is a stereo view showing the loops oriented as they are in the antibody structure. The crystal structure of the Fab fragment of the murine AN02 complexed with its hapten has been solved at 2.9 A resolution using a novel molecular replacement method and the 2.5-A resolution crystal structure of HyHel5 as a search model (Briinger et al, 1991).…”
Section: Analysis Of the Loopsmentioning
confidence: 99%
“…Recently, analysis of known structures by Chothia et al (1989) revealed that there are a small number of main chain conformations found for five of the six hypervariable loops. Evidence indicates that a few conserved residues determine the canonical conformation.…”
mentioning
confidence: 99%